Constructing bioinspired graded metal/ceramic composites through sedimentation-assisted freeze casting and pressure infiltration - Li-Kai Yang; Jin-Hua He; Qiao-Li Lin; Ping Shen (Journal of Materials Research and Technology)
Bioinspired metal/ceramic composites with functionally graded properties were fabricated using sedimentation-assisted freeze casting coupled with pressure infiltration. Employing an Al/(Al2O3+mullite) system as proof of concept, it was demonstrated that these composites exhibited distinctive mechanical characteristics, comprising a hard bottom layer, a tough intermediate layer, and a softer top layer. These properties arise from compositional/structural gradients and complex microstructures. Furthermore, it was established that the graded lamellar structures resulted from the arrangement of stable fibers and mobile particles at the ice crystal front, and composite toughening stems from the synergy between intrinsic and extrinsic mechanisms. This study proposes a scalable route for manufacturing functionally graded materials by integrating established and emerging techniques, offering a viable paradigm for developing innovative bio-inspired synthetic materials.